Selection of Enzymatic Treatments for Upcycling Lentil Hulls into Ingredients Rich in Oligosaccharides and Free Phenolics - Sara Bautista-Expósito; Albert Vandenberg; Montserrat Dueñas; Elena Peñas; Juana Frias; Cristina Martínez-Villaluenga (Molecules, 2022)
In this study, the comprehensive chemical characterization of red lentil hulls obtained from the industrial production of football and split lentils was described. The lentil hulls were rich in dietary fiber (78.43 g/100 g dry weight with an insoluble to soluble fiber ratio of 4:1) and polyphenols (49.3 mg GAE/g dry weight, of which 55% was bound phenolics), which revealed the suitability of this lentil by-product as a source of bioactive compounds with recognized antioxidant and prebiotic properties. The release of oligosaccharides and phenolic compounds was accomplished by enzymatic hydrolysis, microwave treatment and a combination of both technologies. The key role played by the selection of a suitable enzymatic preparation was highlighted to maximize the yield of bioactive compounds and the functional properties of the lentil hull hydrolysates. Out of seven commercial preparations, the one with the most potential for use in a commercial context was Pectinex® Ultra Tropical, which produced the highest yields of oligosaccharides (14 g/100 g lentil hull weight) and free phenolics (45.5 mg GAE/100 g lentil hull weight) and delivered a four-fold increase in terms of the original antioxidant activity. Finally, this enzyme was selected to analyze the effect of a microwave-assisted extraction pretreatment on the yield of enzymatic hydrolysis and the content of free phenolic compounds and oligosaccharides. The integrated microwave and enzymatic hydrolysis method, although it increased the solubilization yield of the lentil hulls (from 25% to 34%), it slightly decreased the content of oligosaccharides and proanthocyanidins and reduced the antioxidant activity. Therefore, the enzymatic hydrolysis treatment alone was more suitable for producing a lentil hull hydrolysate enriched in potential prebiotics and antioxidant compounds.